Markers of bone matebolism during 14 days of bed rest in young and older men - Buehlmeier, J. (2017)
Objective: We aimed at comparing markers of bone metabolism during unloading in young and older men, and toassess countermeasure effectiveness. Methods: 16 older (60±2 years) and 8 younger men (23±3 years) underwentbed rest (BR) for 14 days. A subgroup of the Older performed cognitive training during BR and supplemented proteinand potassium bicarbonate afterwards. Biochemical markers of bone and calcium/phosphate metabolism were assessed.Results: At baseline urinary NTX and CTX were greater in younger than in older subjects (P<0.001), but increased duringBR (P<0.001) by a similar amount (P>0.17). P1NP was greater in young than in older subjects (P<0.001) and decreasedduring BR in the Young (P<0.001). Sclerostin increased during BR across groups (P=0.016). No systematic effects ofthe countermeasure were observed. Conclusion: In men, older age did not affect control of bone metabolism, but boneturnover was reduced. During BR formation markers were reduced only in younger men whereas resorption markersincreased to a comparable extent. Thus, we assume that older men are not at an elevated, and possibly even at a reducedrisk to lose bone when immobilized.